Against proportional shortfall as a priority-setting principle - Altmann, Samuel (Journal of medical ethics, 2018)
As the demand for healthcare rises, so does the need for priority setting in healthcare. In this paper, I consider a prominent priority-setting principle: proportional shortfall. My purpose is to argue that proportional shortfall, as a principle, should not be adopted. My key criticism is that proportional shortfall fails to consider past health.Proportional shortfall is justified as it supposedly balances concern for prospective health while still accounting for lifetime health, even though past health is deemed irrelevant. Accounting for this lifetime perspective means that the principle may indirectly consider past health by accounting for how far an individual is from achieving a complete, healthy life. I argue that proportional shortfall does not account for this lifetime perspective as it fails to incorporate the fair innings argument as originally claimed, undermining its purported justification.I go on to demonstrate that the case for ignoring past health is weak, and argue that past health is at least sometimes relevant for priority-setting decisions. Specifically, when an individual’s past health has a direct impact on current or future health, and when one individual has enjoyed significantly more healthy life years than another.Finally, I demonstrate that by ignoring past illnesses, even those entirely unrelated to their current illness, proportional shortfall can lead to instances of double jeopardy, a highly problematic implication. These arguments give us reason to reject proportional shortfall.